PD-L1 Expression and Its Association With p16 in Head and Neck Squamous Cell Carcinoma in Southwestern Uganda - Nabulya R; Atwine R; Ssenkumba B; Mitala Y; Nabukenya J (Dove Medical Press, 2024)
Rita Nabulya,1 Raymond Atwine,1 Brian Ssenkumba,1 Yekosani Mitala,1 Jamilah Nabukenya2 1Department of Pathology Mbarara University of Science and Technology, Mbarara City, Uganda; 2Department of Ear, Nose and Throat Mbarara University of Science and Technology, Mbarara City, UgandaCorrespondence: Rita Nabulya, Department of Pathology Mbarara University of Science and Technology, Mbarara City, Uganda, Email nabulyarita04@gmail.comPurpose: Head and Neck squamous cell carcinoma (HNSCC) is the seventh most common cancer in the world. The prognosis of patients with HNSCC remains unsatisfactory, with a 5-years survival rate of only approximately 50%. In western Uganda, the 1-year survival rate is only 1%. Programmed cell death ligand 1 (PD-L1) and p16 have been shown to predict the progression of HNSCC lesions, prognosticate survival, reveal new therapeutic targets, and predict response to therapeutic agents. HNSCC patients with positive PD-L1 expression have been reported to benefit from immunotherapy; however, data on PD-L1 expression in HNSCC in Uganda and Africa are still lacking. This study aimed to determine the expression of PD-L1 in HNSCC and its association with p16 expression in Southwestern Uganda.Patients and Methods: We retrospectively studied 165 formalin-fixed paraffin-embedded specimens from the head and neck region with a previous histological diagnosis of squamous cell carcinoma (SCC). The specimens were retrieved from June 2012 to June 2022. Hematoxylin and eosin (H&E) staining was performed to confirm the diagnosis, followed by immunohistochemical (IHC) staining for PD-L1 and p16 using the laboratory developed technique.Results: Of the 165 specimens included in the study, 80% of source patients were male and the majority (51.5%) were older than 60 years. The oral cavity was the predominant site (51.52%). PD-L1 was expressed in 32.1% (95% C.l: 25.4- 39.68) of the specimens, whereas p16 was expressed in 16.36% (95% C.l: 11.4- 22.9). There was a statistically significant association between PD-L1 and p16 expression.Conclusion: The prevalence of PD-L1 expression in HNSCC in southwestern Uganda is low, implying that a number of patients with HNSCC can benefit from immunotherapy. PD-L1 expression may predict p16 expression and therefore HPV infection in HNSCC.Keywords: head and neck squamous cell carcinoma, PD-L1, p16, Uganda